Long-term survival and late events after allogeneic stem cell transplantation from HLA-matched siblings for acute myeloid leukemia with myeloablative compared to reduced-intensity conditioning: a report on behalf of the acute leukemia working party of European group for blood and marrow transplantation. Issue 1 (December 2016) - Shimoni, Avichai; Labopin, Myriam; Savani, Bipin; Volin, Liisa; Ehninger, Gerhard; Kuball, Jurgen; Bunjes, Donald; Schaap, Nicolaas; Vigouroux, Stephane; Bacigalupo, Andrea; Veelken, Hendrik; Sierra, Jorge; et al.
Abstract Background Myeloablative (MAC) and reduced-intensity conditioning (RIC) are established approaches for allogeneic stem cell transplantation (SCT) in acute myeloid leukemia (AML). Most deaths after MAC occur within the first 2 years after SCT, while patients surviving leukemia-free for 2 years can expect a favorable long-term outcome. However, there is paucity of data on the long-term outcome (beyond 10 years) and the pattern of late events following RIC due to the relative recent introduction of this approach. Methods We analyzed long-term outcomes in a cohort of 1423 AML patients, age ≥50 years, after SCT from HLA-matched siblings, during the years 1997–2005, median follow-up 8.3 years (0.1–17). Results The 10-year leukemia-free survival (LFS) was 31 % (95CI, 27–35) and 32 % (28–35) after MAC and RIC, respectively (P = 0.57). The 10-year GVHD/ relapse-free survival (GRFS), a surrogate for quality of life was 22 % (18–25) and 21 % (18–24), respectively (P = 0.79). The 10-year non-relapse mortality (NRM) was higher and relapse rate was lower after MAC, throughout the early and late post-transplant course. The 10-year LFS among 584 patients surviving leukemia-free 2 years after SCT was 71 % (65–76) and 73 % (67–78) after MAC and RIC, respectively (P = 0.76). Advanced leukemia at SCT was the major predictor of LFS subsequent to the 2-year landmark. Relapse was the major cause of late death after both regimens; however, NRM and in particular chronic graft-versus-host disease and second cancers were more common causes of late death after MAC. Conclusions Long-term LFS and GRFS are similar after RIC and MAC. Most events after RIC or MAC occur within the first 2 years after SCT. Patients who are leukemia-free 2 years after SCT can expect similar good subsequent outcome after both approaches.